A high-strength and tough zinc alloy with prefabricated quasi-microcrack petal-shaped tough second phase and its preparation method and application

By introducing a prefabricated quasi-microcrack petal-like tough second phase into the zinc alloy and through multiple equal-channel angle extrusion processing, an ultrafine crystal matrix and a high-density dislocation network-like second phase is formed, the problem of difficulty in matching the strength and toughness of the zinc alloy is solved, and the strength and toughness of the alloy is significantly improved.

CN119194166BActive Publication Date: 2025-03-21HOHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411305733.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-03-21
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The strength and toughness of existing zinc alloys are difficult to match, mainly because the increase in the content of the effective reinforced phase will reduce the plasticity of the alloy, and the difference in modulus and poor coordinated deformation ability of the reinforced phase and the matrix lead to rapid formation and expansion of cracks.

Method used

A high-strength tough zinc alloy with a prefabricated quasi-microcrack petal-like tough second phase is used to introduce a second phase of petal-like GdZn12 or NdZn11 with a volume fraction of 3 to 10% and an average size distribution of 5 to 40 μm into the alloy, and through multiple equal-channel angle extrusion processing, an ultrafine crystal matrix and a high-density dislocation network-like second phase is formed to prevent cracks from emerging and expanding at the interface.

Benefits of technology

The strength and toughness of the zinc alloy are significantly improved, cracks are prevented from spreading through the toughness and deformation coordination ability of the petal-like second phase, and energy absorption capacity is improved by the generation of cracks by itself, which is better than the corresponding zinc alloy without the petal-like second phase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194166B_ABST
    Figure CN119194166B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and tough zinc alloy with prefabricated quasi-microcrack petal-shaped tough second phase and its preparation method and application, belonging to the technical field of zinc alloy material processing. The high-strength and tough zinc alloy microstructure contains 3-10% volume fraction and 5-40μm average size distribution of prefabricated quasi-microcrack petal-shaped GdZn 12 Phase or NdZn 11 The second phase, or a mixture of two second phases, has an average grain size of 0.5 to 1.2 μm in the matrix grains of the alloy. The degradable zinc alloy of the present invention has both high strength and high toughness. The present invention utilizes the good toughness and deformation coordination ability of the petal-shaped second phase to prevent cracks from initiating at the interface between the second phase and the matrix. At the same time, the petal-shaped second phase can improve the energy absorption capacity by generating cracks by itself, that is, improve the strength and toughness of the zinc alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength and toughness zinc alloy with a prefabricated quasi-microcrack petal-shaped toughness second phase and a preparation method and application thereof, belonging to the technical field of zinc alloy material processing. Background Art

[0002] Zinc alloy has become the most popular biodegradable metal material in recent years due to its moderate degradation rate, certain mechanical properties and good processability. In addition, zinc is an essential element for the human body, an important component of more than 200 enzymes in the human body, and is widely distributed in human bones, muscles and internal organs. Zinc deficiency can affect children's physical growth, affect the development of the nervous system, and reduce human immunity. Therefore, biodegradable medical devices made of zinc can not only meet their own functions, but also effectively improve zinc deficiency.

[0003] However, the current application of zinc is far less than that of magnesium, iron and their alloys. One of the main reasons is that the mechanical properties of pure zinc are poor, and its mechanical properties need to be further improved to meet the mechanical property requirements of degradable medical devices such as orthopedic implants and cardiovascular implants (mainly including tensile yield strength, tensile strength and elongation). The main methods currently used are alloying and plastic processing deformation. The alloying elements include magnesium, copper, manganese, silver, lithium, etc., and the plastic processing methods include traditional extrusion, rolling and severe plastic processing. Although some zinc-based alloys that meet the mechanical property requirements have been developed, a large number of reported zinc alloys still have the problem of difficulty in matching strength and toughness. The main reason is that the effective strengthening phase in the zinc alloy (such as Mg2Zn 11 The increase of its content will rapidly reduce the plasticity of the alloy. Due to the large difference in the modulus of the reinforcing phase and the matrix and the poor coordination deformation ability of the two, cracks will form and expand rapidly between the interface of the reinforcing phase and the matrix. Therefore, it is necessary to further explore the appropriate reinforcing phase and toughening structure in zinc alloys and develop degradable zinc alloys with both high strength and high toughness. Summary of the invention

[0004] The present invention provides a high-strength and toughness zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase. The degradable zinc alloy has both high strength and high toughness. The present invention utilizes the good toughness and deformation coordination ability of the petal-shaped second phase to hinder the initiation of cracks from the interface between the second phase and the matrix. At the same time, the petal-shaped second phase can improve the energy absorption capacity by generating cracks by itself, that is, improve the strength and toughness of the zinc alloy.

[0005] At the same time, the present invention provides a method for preparing a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase. The method is based on the ultrafine matrix, self-toughening and interface coordination produced by the petal-shaped second phase, which effectively hinders the initiation and propagation of cracks at the interface during loading of the alloy, and significantly improves the strength and toughness of the alloy.

[0006] At the same time, the present invention provides an application of a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase in degradable medical devices such as orthopedic implants and cardiovascular implants.

[0007] At the same time, the present invention provides an application of a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase in biomedical degradable metal materials.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase, wherein the alloy microstructure contains 3-10% volume fraction of prefabricated quasi-microcrack petal-shaped GdZn with an average size distribution of 5-40 μm 12 Phase or NdZn 11 The second phase, or a mixture of two second phases, has an average grain size of 0.5 to 1.2 μm in the matrix grains of the alloy.

[0010] Preferably, the zinc alloy includes the following alloy series: Zn-Cu-Gd, Zn-Cu-Nd, Zn-Mg-Gd, Zn-Mg-Nd, Zn-Cu-Mg-Gd, Zn-Cu-Mg-Nd, Zn-Cu-Gd-Nd, Zn-Mg-Gd-Nd and Zn-Cu-Mg-Gd-Nd.

[0011] Preferably, the mass percentages of alloying elements in the zinc alloy meet the following requirements: Cu: 0.5-3.5%, Mg: 0.5-1.2%, Gd: 0.2-0.5% and / or Nd: 0.2-0.6%, and the sum of Gd+Nd content meets: 0.2-0.6%, with the balance being Zn.

[0012] A method for preparing a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase comprises the following steps:

[0013] S01, preparing a zinc ingot, and performing a primary smelting under the protection of an inert atmosphere, the primary smelting temperature being 400-420° C., after the zinc ingot is melted, adding pure copper and pure magnesium, and standing for at least 20 minutes before pouring to obtain a primary ingot;

[0014] S02, performing secondary smelting on the primary ingot under an inert atmosphere at a temperature of 600-650° C., adding pure Gd and / or pure Nd after the primary ingot is melted, mechanically stirring for 10-30 minutes, and then rapidly cooling and solidifying to obtain a secondary ingot, i.e., a cast alloy;

[0015] The rate of rapid cooling and solidification is 80-120℃ / s;

[0016] S03, subjecting the secondary ingot to one high-temperature equal channel angular extrusion process; the angle of the die for high-temperature equal channel angular extrusion is 135°, the processing temperature is 280-300°C, the temperature is kept at 280-300°C for at least 30 minutes before processing, and the sample is water-cooled after processing;

[0017] S04, subjecting the alloy processed by S03 to one pass of medium-temperature equal channel angular extrusion; the angle of the die of the medium-temperature equal channel angular extrusion is 120°, the processing temperature is 200-220°C, the temperature is kept at 200-220°C for at least 30 minutes before processing, and the sample is water-cooled after processing;

[0018] S05, the alloy processed by S04 is subjected to one low-temperature equal channel angular extrusion process, the corner arc of the die of the low-temperature equal channel angular extrusion is 90°, the processing temperature is 120-140°C, and the temperature is kept at 120-140°C for at least 30 minutes before processing. After processing, the sample is water-cooled to obtain a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase.

[0019] Preferably, in S01 and S02, the inert atmosphere is a mixed gas of CO2 and FS6 at a ratio of 99:1.

[0020] Preferably, in S03, S04 and S05, the water cooling temperature is 10-25°C.

[0021] Preferably, in S02, the mechanical stirring time t satisfies: t=5×(mass percentage of Gd+Nd)×1000 minutes.

[0022] Application of a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase in biomedical degradable metal materials.

[0023] Preferably, the biomedical degradable metal material includes degradable medical devices, and the degradable medical devices include orthopedic implant devices and cardiovascular implant devices.

[0024] A biomedical degradable metal material is prepared from a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase according to the present invention.

[0025] The beneficial effects achieved by the present invention are:

[0026] (1) Using equal channel angular extrusion processing with relatively low passes to obtain ultrafine grain size and improve the toughness of the matrix: Refining zinc alloy by equal channel angular extrusion requires relatively high processing passes (greater than 8 passes). The present invention uses a petal-shaped second phase with a certain volume fraction of 3% to 10% and an average size distribution of 5 to 40 μm to fully exert the dynamic recrystallization nucleation mechanism of the matrix stimulated by hard second phase particles. The equal channel angular extrusion processing is carried out for three times at high temperature of 280 to 300°C and an angle of 135°, medium temperature of 200 to 220°C and an angle of 120°, and low temperature of 120 to 140°C and an angle of 90° to obtain a completely recrystallized ultrafine grain structure with a recrystallized grain size of 0.5 to 1.2 μm. The ultrafine grain structure can significantly improve the toughness of the matrix.

[0027] (2) The present invention obtains a petal-shaped second phase containing prefabricated high-density dislocations, improves the energy absorption capacity of the second phase, and increases the toughness of the alloy: the present invention performs one high-temperature (280-300°C) equal-channel 135° angular extrusion on the alloy that has been homogenized after secondary melting, which can refine the matrix to a certain extent and improve the deformation capacity of the matrix. At the same time, an appropriate amount of dislocations are introduced between the interface of the petal-shaped second phase and the matrix to soften the second phase; then, one pass of equal-channel 120° angular extrusion is performed at a medium temperature (200-220°C), which, on the one hand, intensifies the particle stimulation nucleation of the petal-shaped second phase and promotes the dynamic recrystallization of the matrix. On the other hand, during the severe plastic deformation at the medium temperature, the dislocations at the interface between the petal-shaped second phase and the matrix will continue to expand into the second phase. Finally, during one low-temperature (120-140°C) equal-channel 90° angular extrusion process, the zinc matrix reaches an ultra-fine level, and dislocations are further accumulated in the petal-shaped second phase, forming high-density dislocations connected in a network (which can be regarded as quasi-microcracks). Since the petal-shaped second phase has been softened during high-temperature and medium-temperature processing, no obvious macroscopic microcracks will be formed during low-temperature equal-channel angular extrusion processing. When a high-strength and tough zinc alloy with a prefabricated microcracked petal-shaped tough second phase is obtained during service or stretching, the network-like high-density dislocations formed inside the petals, on the one hand, hinder the movement of dislocations, improve the strength of the alloy, and can further entangle a large number of dislocations to produce sufficient work hardening and improve toughness; on the other hand, when the dislocation density reaches a certain level, microcracks can be formed quasi-in-situ. Since the high-density dislocations accumulated simultaneously in the tough phase can promote the formation of multi-source microcracks, the interconnected expansion of microcracks hinders the widening of cracks and the rapid expansion of a certain crack, and this process absorbs the energy generated by stretching, further improving the strength and toughness of the alloy;

[0028] (3) The present invention improves the deformation coordination between the petal-shaped second phase and the matrix: Since a high-density network of dislocations is prefabricated in the petal-shaped second phase, the newly added dislocations preferentially expand in the petal-shaped second phase during stretching. Although there is still a large difference in elastic modulus between the second phase and the matrix, the dislocations generated by the deformation mismatch at the interface can expand into the petal-shaped second phase, so the cracking at the interface is effectively suppressed. In addition, when the microcracks in the second phase expand to the interface area, the ultrafine grain boundaries can passivate the microcracks, thereby prolonging the crack penetration time.

[0029] In summary, the ultrafine matrix, self-toughening and interface coordination produced by the petal-shaped second phase effectively hinder the initiation and propagation of cracks at the interface during loading, significantly improve the strength and toughness of the alloy, which is better than the corresponding zinc alloy without the petal-shaped second phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM photo of the cast alloy, where the black arrows indicate the petal-shaped second phase, with a size distribution of 5 to 40 μm and a content of 3% to 10%;

[0031] Figure 2 This is a SEM photograph of a network-like high-density dislocation petal-shaped second phase produced in a deformed zinc alloy obtained by the technical solution of the present invention. It can be seen that after equal channel angular extrusion processing, the petal-shaped second phase still maintains structural integrity without obvious cracking;

[0032] Figure 3 yes Figure 2 The TEM image of the petal-shaped second phase shows that there are a large number of high-density dislocations inside the petal-shaped second phase, and some of the dislocations are entangled with each other to form a network.

[0033] Figure 4 This is an EBSD image of the matrix in the deformed zinc alloy obtained by using the technical solution of Example 1 of the present invention. It can be seen that the average grain size of the matrix is ​​0.9 microns, which is an ultrafine grain structure;

[0034] Figure 5 This is a TEM photo of the matrix in the deformed zinc alloy. It can be seen that the grain structure of some of the matrix is ​​less than 0.5 microns;

[0035] Figure 6This is a SEM photograph of the petal-shaped second phase in the vicinity of the fracture of the deformed zinc alloy obtained by the technical solution of the present invention after tensile fracture. It can be seen that a large number of visible microcracks are generated in the petal-shaped second phase, and some of the microcracks merge and interact, indicating that the petal-shaped second phase absorbs a large amount of energy; in addition, it can be seen that the cracks extending to the boundary of the petal-shaped second phase stop expanding, and the phase boundary between the surface second phase and the matrix can hinder the further expansion of the microcracks, further indicating the toughening effect of the second phase in the present invention;

[0036] Figure 7 This is a picture of the alloy in Comparative Example 2 breaking during the extrusion process. DETAILED DESCRIPTION

[0037] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0038] Example 1

[0039] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase, wherein the mass percentages of alloy elements in the zinc alloy are: Cu: 3.0%, Mg: 1.0%, Nd: 0.3% and the balance Zn.

[0040] A method for preparing a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase comprises the following steps:

[0041] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0042] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0043] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die of the high temperature equal channel angular extrusion is 135°, the processing temperature is 280°C, the temperature is kept at 280°C for 30 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 10°C;

[0044] S04, the alloy processed by S03 is subjected to one pass of medium temperature equal channel angular extrusion; the angle of the die of the medium temperature equal channel angular extrusion is 120°, the processing temperature is 200°C, and the temperature is kept at 200°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0045] S05, the alloy processed by S04 was subjected to one low-temperature equal channel angular extrusion process. The corner arc of the die of the low-temperature equal channel angular extrusion was 90°, the processing temperature was 120°C, and it was kept at 120°C for 30 minutes before processing. After processing, the sample was water-cooled at a temperature of 10°C to obtain a high-strength and tough zinc alloy with a prefabricated micro-crack petal-shaped tough second phase.

[0046] In S02, the mechanical stirring time t satisfies: t = 5 × (mass percentage of Nd) × 1000 minutes. After calculation, the mechanical stirring time is 15 minutes.

[0047] The high-strength and tough zinc alloy with prefabricated microcrack petal-shaped tough second phase of the present embodiment is used, and the alloy microstructure contains 6.5% volume fraction and 20.6 μm average size distribution of prefabricated microcrack petal-shaped NdZn 11 The average grain size of the second phase, the matrix grains in the alloy, is 0.9 μm.

[0048] Application of a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase in biomedical degradable metal materials.

[0049] Biomedical degradable metal materials include degradable medical devices, which include orthopedic implants and cardiovascular implants.

[0050] A biomedical degradable metal material is prepared from a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase according to the embodiment.

[0051] Implementation 2

[0052] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase, wherein the mass percentages of alloy elements in the zinc alloy are: Cu: 0.5%, Mg: 0.5%, Gd: 0.2%, Nd: 0.2% and the balance Zn.

[0053] A method for preparing a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase comprises the following steps:

[0054] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 420°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 30 minutes, and then cast it to obtain a primary ingot;

[0055] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 650°C. After the primary ingot is melted, pure Gd and pure Nd are added, mechanically stirred for 20 minutes, and then rapidly cooled and solidified at 80°C / s to obtain a secondary ingot, i.e., a cast alloy;

[0056] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die of the high temperature equal channel angular extrusion is 135°, the processing temperature is 300°C, the temperature is kept at 300°C for 40 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 25°C;

[0057] S04, the alloy processed by S03 is subjected to one pass of medium temperature equal channel angular extrusion; the angle of the die of the medium temperature equal channel angular extrusion is 120°, the processing temperature is 220°C, and the temperature is kept at 220°C for 35 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 25°C;

[0058] S05, the alloy processed by S04 was subjected to one low-temperature equal channel angular extrusion process. The corner arc of the die of the low-temperature equal channel angular extrusion was 90°, the processing temperature was 140°C, and it was kept at 140°C for 40 minutes before processing. After processing, the sample was water-cooled at a temperature of 25°C to obtain a high-strength and tough zinc alloy with a prefabricated micro-crack petal-shaped tough second phase.

[0059] In S02, the mechanical stirring time t satisfies: t = 5 × (mass percentage of Gd + Nd) × 1000 minutes. After calculation, the mechanical stirring time is 20 minutes.

[0060] The high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase of the present embodiment is used, and the alloy microstructure contains petal-shaped GdZn with a volume fraction of 7.8% and an average size distribution of 28.9 μm. 12 Phase and NdZn 11 The average grain size of the matrix grains in the alloy is 1.0 μm.

[0061] Application of a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase in biomedical degradable metal materials.

[0062] Biomedical degradable metal materials include degradable medical devices, which include orthopedic implants and cardiovascular implants.

[0063] A biomedical degradable metal material is prepared from a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase according to the embodiment.

[0064] Example 3

[0065] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase, wherein the mass percentages of alloy elements in the zinc alloy are: Cu: 3.5%, Mg: 1.2%, and Gd: 0.5%.

[0066] A method for preparing a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase comprises the following steps:

[0067] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 410°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 35 minutes, and then cast it to obtain a primary ingot;

[0068] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 620°C. After the primary ingot is melted, pure Gd is added, mechanically stirred for 25 minutes, and then rapidly cooled and solidified at 120°C / s to obtain a secondary ingot, i.e., a cast alloy;

[0069] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die for high temperature equal channel angular extrusion is 135°, the processing temperature is 290°C, the temperature is kept at 290°C for 30 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 20°C;

[0070] S04, the alloy processed by S03 was subjected to one pass of medium temperature equal channel angular extrusion; the angle of the die of the medium temperature equal channel angular extrusion was 120°, the processing temperature was 210°C, and the temperature was kept at 210°C for 35 minutes before processing. After processing, the sample was water-cooled at a water cooling temperature of 15°C;

[0071] S05, the alloy processed by S04 was subjected to one low-temperature equal channel angular extrusion process. The corner arc of the die of the low-temperature equal channel angular extrusion was 90°, the processing temperature was 130°C, and the temperature was kept at 130°C for 30 minutes before processing. After processing, the sample was water-cooled at a temperature of 15°C to obtain a high-strength and tough zinc alloy with a prefabricated micro-crack petal-shaped tough second phase.

[0072] In S02, the mechanical stirring time t satisfies: t = 5 × (mass percentage of Gd + Nd) × 1000 minutes. After calculation, the mechanical stirring time is 25 minutes.

[0073] The high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase of this embodiment is used, and the alloy microstructure contains petal-shaped GdZn with a volume fraction of 9% and an average size distribution of 25.4 μm. 12Phase, the average grain size of the matrix grains in the alloy is 0.8μm.

[0074] Application of a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase in biomedical degradable metal materials.

[0075] Biomedical degradable metal materials include degradable medical devices, which include orthopedic implants and cardiovascular implants.

[0076] A biomedical degradable metal material is prepared from a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase according to the embodiment.

[0077] Example 4

[0078] The difference between this embodiment and embodiment 1 is only that:

[0079] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase, wherein the mass percentages of alloy elements in the zinc alloy are: Cu: 3.0%, Mg: 1.0%, Nd: 0.2% and the balance Zn.

[0080] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase is used in this embodiment. The alloy microstructure contains petal-shaped NdZn with a volume fraction of 3% and an average size distribution of 5 μm. 11 Phase, the average grain size of the matrix grains in the alloy is 0.5μm.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is only that:

[0083] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase. The mass percentages of alloy elements in the zinc alloy are: Cu: 3.0%, Mg: 1.0%, Nd: 0.6% and the balance Zn.

[0084] A high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase is used in this embodiment. The alloy microstructure contains petal-shaped NdZn with a volume fraction of 10% and an average size distribution of 40 μm. 11 Phase, the average grain size of the matrix grains in the alloy is 1.2μm.

[0085] Comparative Example 1 (High-temperature 3-pass equal-channel angular extrusion process)

[0086] The difference between this comparative example and Example 1 is only that:

[0087] A method for preparing a zinc alloy comprises the following steps:

[0088] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0089] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0090] S03, the secondary ingot is subjected to three passes of high temperature equal channel angular extrusion processing; the corner arc of the high temperature equal channel angular extrusion mold is 135°, the processing temperature is 280°C, and it is kept at 280°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C.

[0091] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown, marked by the black arrow, has an average size of 20.6 μm and a content of 6.5%. However, after three high-temperature equal channel angular extrusion processes, the comparative example 1 did not prefabricate high-density network dislocations in the petal-shaped second phase, and the grain size of the alloy did not reach ultrafine grains.

[0092] Comparative Example 2 (3-pass equal channel angular extrusion at medium temperature)

[0093] The difference between this comparative example and Example 1 is only that:

[0094] A method for preparing a zinc alloy comprises the following steps:

[0095] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0096] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0097] S03, the secondary ingot is subjected to three passes of medium-temperature equal channel angular extrusion processing; the angle of the die of the medium-temperature equal channel angular extrusion is 120°, the processing temperature is 200°C, and the temperature is kept at 200°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0098] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown in the figure is marked by a black arrow, and its average size is 20.6 μm and its content is 6.5%. However, after three times of medium-temperature equal channel angular extrusion processing, the high-density network dislocations in the petal-shaped second phase were not prefabricated, so that the cracking at the interface could not be suppressed. Figure 7 As shown, the zinc alloy obtained in this comparative example broke during the extrusion process, while the zinc alloy obtained in Example 1 did not break during the extrusion process.

[0099] Comparative Example 3 (Low-temperature 3-pass equal-channel angular extrusion process)

[0100] The difference between this comparative example and Example 1 is only that:

[0101] A method for preparing a zinc alloy comprises the following steps:

[0102] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0103] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0104] S03, the secondary ingot is subjected to three passes of low temperature equal channel angular extrusion processing; the corner arc of the die of low temperature equal channel angular extrusion is 90°, the processing temperature is 120°C, and the temperature is kept at 120°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0105] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown, marked by the black arrow, has an average size of 20.6 μm and a content of 6.5%. However, after three low-temperature equal channel angular extrusion processes, the comparative example 3 did not prefabricate a high-density network of dislocations in the petal-shaped second phase, so that the cracking at the interface could not be suppressed, and the zinc alloy obtained in this comparative example also broke during the extrusion process.

[0106] Comparative Example 4 (High temperature, medium temperature, and medium temperature three-pass equal channel angular extrusion processing)

[0107] The difference between this comparative example and Example 1 is only that:

[0108] A method for preparing a zinc alloy comprises the following steps:

[0109] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0110] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0111] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die of the high temperature equal channel angular extrusion is 135°, the processing temperature is 280°C, the temperature is kept at 280°C for 30 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 10°C;

[0112] S04, the alloy processed by S03 is subjected to one pass of medium temperature equal channel angular extrusion; the angle of the die of the medium temperature equal channel angular extrusion is 120°, the processing temperature is 200°C, and the temperature is kept at 200°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0113] S05, the alloy processed by S04 is subjected to one medium-temperature equal channel angular extrusion process. The corner arc of the die of the medium-temperature equal channel angular extrusion is 120°, the processing temperature is 200°C, and it is kept at 200°C for 30 minutes before processing. After processing, the sample is water-cooled at a water cooling temperature of 10°C.

[0114] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown, marked by the black arrow, has an average size of 20.6 μm and a content of 6.5%. However, after three times of high temperature, medium temperature, and medium temperature equal channel angular extrusion processing, the comparative example 4 did not preform a high-density network of dislocations in the petal-shaped second phase.

[0115] Comparative Example 5 (High temperature, low temperature, low temperature three-pass equal channel angular extrusion processing)

[0116] The difference between this comparative example and Example 1 is only that:

[0117] A method for preparing a zinc alloy comprises the following steps:

[0118] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0119] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0120] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die of the high temperature equal channel angular extrusion is 135°, the processing temperature is 280°C, the temperature is kept at 280°C for 30 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 10°C;

[0121] S04, the alloy processed by S03 is subjected to one low temperature equal channel angular extrusion process; the angle of the die of the low temperature equal channel angular extrusion is 90°, the processing temperature is 120°C, and the temperature is kept at 120°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0122] S05, the alloy processed by S04 is subjected to one low-temperature equal channel angular extrusion process. The corner arc of the die of the low-temperature equal channel angular extrusion is 90°, the processing temperature is 120°C, and it is kept at 120°C for 30 minutes before processing. After processing, the sample is water-cooled at a water cooling temperature of 10°C.

[0123] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown, marked by the black arrow, has an average size of 20.6 μm and a content of 6.5%. However, after three times of high-temperature, low-temperature, and low-temperature channel angular extrusion processing, the comparative example 5 did not prefabricate high-density network dislocations in the petal-shaped second phase, but instead had a large number of microcracks.

[0124] Comparative Example 6 (3-pass equal channel angular extrusion process at high temperature 90°, medium temperature 120°, and low temperature 135°)

[0125] The difference between this comparative example and Example 1 is only that:

[0126] A method for preparing a zinc alloy comprises the following steps:

[0127] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 400°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0128] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1) at a temperature of 600°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 15 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain a cast alloy.

[0129] S03, the secondary ingot is subjected to one high temperature equal channel angular extrusion process; the angle of the die of the high temperature equal channel angular extrusion is 90°, the processing temperature is 280°C, the temperature is kept at 280°C for 30 minutes before processing, and the sample is water-cooled after processing, and the water cooling temperature is 10°C;

[0130] S04, the alloy processed by S03 is subjected to one pass of medium temperature equal channel angular extrusion; the angle of the die of the medium temperature equal channel angular extrusion is 120°, the processing temperature is 200°C, and the temperature is kept at 200°C for 30 minutes before processing. After processing, the sample is water-cooled, and the water cooling temperature is 10°C;

[0131] S05: The alloy processed by S04 was subjected to one low-temperature equal channel angular extrusion process. The angle of the die for low-temperature equal channel angular extrusion was 135°, the processing temperature was 120°C, and the sample was kept at 120°C for 30 minutes before processing. After processing, the sample was water-cooled at a temperature of 10°C.

[0132] In this comparative example, the cast alloy was obtained by two smeltings. The cast alloy contains Figure 1 The petal-shaped second phase shown, marked by the black arrow, has an average size of 20.6 μm and a content of 6.5%. However, after three times of 90° high temperature, 120° medium temperature, and 135° low temperature equal channel angular extrusion processing, the comparative example 6 did not prefabricate high-density network dislocations in the petal-shaped second phase, but instead had a large number of microcracks, and the alloy structure did not reach ultrafine grains.

[0133] Comparative Example 7

[0134] The difference between this comparative example and Example 1 is only that:

[0135] A method for preparing a zinc alloy comprises the following steps:

[0136] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 450°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0137] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 in a ratio of 99:1) at a temperature of 550°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 20 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain the cast alloy.

[0138] A zinc alloy of the present comparative example is used, and the alloy microstructure contains a petal-shaped second phase with a volume fraction of about 15% and an average size distribution of about 75 μm. After the phase is subjected to three equal-channel angular extrusion processes of high temperature, medium temperature, and low temperature in Example 1, high-density network dislocations are not prefabricated in the petal-shaped second phase.

[0139] Comparative Example 8

[0140] The difference between this comparative example and Example 1 is only that:

[0141] A method for preparing a zinc alloy comprises the following steps:

[0142] S01, prepare a zinc ingot, perform a smelting operation under the protection of an inert atmosphere (a mixture of CO2 and FS6 at a ratio of 99:1), the temperature of the smelting operation is 370°C, after the zinc ingot is melted, add pure copper and pure magnesium, let it stand for 20 minutes, and then cast it to obtain a primary ingot;

[0143] S02, the primary ingot is subjected to secondary smelting in an inert atmosphere (a mixture of CO2 and FS6 in a ratio of 99:1) at a temperature of 680°C. After the primary ingot is melted, pure Nd is added, and after mechanical stirring for 5 minutes, the secondary ingot is rapidly cooled and solidified at 100°C / s to obtain the cast alloy.

[0144] A zinc alloy of the present comparative example is used, and the alloy microstructure contains a petal-shaped second phase with a volume fraction of about 1.2% and an average size distribution of about 3 μm. After the phase is subjected to three equal-channel angular extrusion processes of high temperature, medium temperature, and low temperature in Example 1, high-density network dislocations are not prefabricated in the petal-shaped second phase.

[0145] The microstructures of the above alloys were characterized. Figure 1 The figure shows the SEM photo of the alloy of Example 1 after S01 casting, in which the petal-shaped phase marked by the arrow is NdZn 11 The size and content of the second phase were counted using Image J software, and the average size was 20.6 μm and the content was 6.5%.

[0146] Figure 2 This is the SEM photo of the alloy obtained in Example 1. It can be seen that many ups and downs wrinkles are generated in the petal-shaped second phase. In the TEM photo ( Figure 3 ) determined that these wrinkles are actually high-density network dislocations, which can be regarded as prefabricated quasi-microcracks.

[0147] Figure 4 This is the EBSD image of the matrix region in the alloy obtained in Example 1. It can be seen that the alloy matrix is ​​ultrafine-grained with an average grain size of 0.9 μm. Figure 5 This is the TEM picture of the matrix, which further proves the ultrafine grain structure of the matrix.

[0148] Figure 6 This is a SEM photograph of the petal-like phase observed near the fracture of the tensile specimen of the alloy of Example 1 after room temperature stretching. It can be seen that during the stretching process, many microcracks appeared inside the petal-like phase, and the microcracks contacted each other and hindered their rapid expansion; in addition, it can be seen that these microcracks terminated at the interface between the petal-like second phase and the matrix after passing through the petal-like phase, and they were not seen to extend through the interface in the matrix. The surface petal-like second phase itself and its interface with the matrix can effectively hinder the expansion of cracks and absorb a large amount of energy, thereby improving the strength and toughness of the alloy.

[0149] Figure 7 This is the macroscopic morphology of the zinc alloy obtained in Comparative Example 2. Due to the high temperature of the equal channel transfer extrusion process, the sample was cracked after three passes of processing, and the sample could not be successfully obtained.

[0150] In order to compare the room temperature tensile mechanical properties of each embodiment and the comparative example, each alloy was stretched at room temperature according to the national standard GB / T228.1-2021, and its performance is summarized as follows. As can be seen from Table 1, the alloys in Examples 1-3 have obtained a good combination of strength (tensile strength) and toughness (elongation at break), and the comprehensive toughness can be significantly better than the comparative example (the alloy preparation process of Comparative Example 2 to Comparative Example 3 has been broken, indicating that its plastic toughness is very poor). In Comparative Example 1, due to the lack of high-density network dislocation aggregation in the petal-shaped second phase, the alloy is easily formed at the interface between the second phase and the matrix during stretching and rapidly expands along the matrix or the second phase, causing the alloy to break. Therefore, the petal-shaped second phase containing high-density network dislocations in the alloy obtained by the present invention has a significant strengthening and toughening effect.

[0151] Table 1 Room temperature tensile mechanical properties of the alloys of the examples and comparative examples

[0152] alloy Tensile strength / MPa Elongation at break / % Example 1 478 34 Example 2 396 46 Example 3 489 27 Example 4 432 51 Example 5 486 35 Comparative Example 1 353 19 Comparative Example 4 357 13 Comparative Example 5 369 16 Comparative Example 6 345 15 Comparative Example 7 353 16 Comparative Example 8 362 17

[0153] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0154] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0155] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase, characterized in that: The alloy microstructure contains 3-10% volume fraction of petal-shaped GdZn with prefabricated quasi-microcracks and an average size distribution of 5-40 μm. 12 Phase or NdZn 11 The second phase, or a mixture of two second phases, has an average grain size of 0.5 to 1.2 μm for the matrix grains in the alloy; The mass percentage of alloying elements in the zinc alloy meets the following requirements: Cu: 0.5-3.5%, Mg: 0.5-1.2%, Gd: 0.2-0.5% and / or Nd: 0.2-0.6%, and the sum of Gd+Nd content meets: 0.2-0.6%, with the balance being Zn; The preparation method comprises the following steps: S01, preparing a zinc ingot, and performing a primary smelting under the protection of an inert atmosphere, the primary smelting temperature being 400-420° C., after the zinc ingot is melted, adding pure copper and pure magnesium, and standing for at least 20 minutes before pouring to obtain a primary ingot; S02, performing secondary smelting on the primary ingot under an inert atmosphere at a temperature of 600-650° C., adding pure Gd and / or pure Nd after the primary ingot is melted, mechanically stirring for 10-30 minutes, and then rapidly cooling and solidifying to obtain a secondary ingot, i.e., a cast alloy; S03, subjecting the secondary ingot to one high-temperature equal channel angular extrusion process; the angle of the die for high-temperature equal channel angular extrusion is 135°, the processing temperature is 280-300°C, the temperature is kept at 280-300°C for at least 30 minutes before processing, and the sample is water-cooled after processing; S04, subjecting the alloy processed by S03 to one pass of medium-temperature equal channel angular extrusion; the angle of the die of the medium-temperature equal channel angular extrusion is 120°, the processing temperature is 200-220°C, the temperature is kept at 200-220°C for at least 30 minutes before processing, and the sample is water-cooled after processing; S05, the alloy processed by S04 is subjected to one low-temperature equal channel angular extrusion process, the corner arc of the die of the low-temperature equal channel angular extrusion is 90°, the processing temperature is 120-140°C, and the temperature is kept at 120-140°C for at least 30 minutes before processing. After processing, the sample is water-cooled to obtain a high-strength and tough zinc alloy with a prefabricated quasi-microcrack petal-shaped tough second phase.

2. The preparation method according to claim 1, characterized in that: In S01 and S02, the inert atmosphere is a mixture of CO2 and FS6 at a ratio of 99:

1.

3. The preparation method according to claim 1, characterized in that: In S03, S04 and S05, the water cooling temperature is 10 to 25°C.

4. The preparation method according to claim 1, characterized in that: In S02, the mechanical stirring time t satisfies: t=5×(mass percentage of Gd+Nd)×1000 minutes.

5. Application of a high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase obtained by the preparation method according to any one of claims 1 to 4 in biomedical degradable metal materials.

6. The use according to claim 5, characterized in that: Biomedical degradable metal materials include degradable medical devices, which include orthopedic implants and cardiovascular implants.

7. A biomedical degradable metal material, characterized in that: A high-strength and tough zinc alloy having a prefabricated quasi-microcrack petal-shaped tough second phase obtained by the preparation method described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Zn-RE series zinc alloy as well as preparation method and application thereof

    CN111334688A

  • High-toughness degradable zinc alloy with layered ultra-fine grain structure as well as preparation method and application of high-toughness degradable zinc alloy

    CN113183561A